In-home work environment for home care workers in Northern Sweden before and during the Covid-19 pandemic - Fredrik Norström; Karin Bölenius; Klas-Göran Sahlén; Magnus Zingmark; Anita Pettersson-Strömbäck (BMC Health Services Research)
Abstract Background The in-home work environment is the main work environment for home care workers, but it has only been sparsely studied. Our aim was to investigate the in-home work environment for home care workers by exploring challenges that arise regardless of a pandemic and by investigating Covid-19–specific challenges. Methods Two cross-sectional studies were conducted, one before (2017) and one during the pandemic (2021/2022) in three Swedish regions (Jämtland/Härjedalen, Västerbotten and Västernorrland), in which 1,154 (58%) out of 2,000 and 629 (33%) of 1,900 invited home care workers participated, respectively. Participants responded to a questionnaire asking about 10 problems associated with the in-home work environment as well as Covid-19–related challenges. Comparisons were conducted between regions and between study years using univariable analyses. Results Daily problems with the in-home work environment were common before the pandemic, and they increased statistically significantly during the pandemic for, among other things, non-ergonomic beds (29% vs. 37%), impractical bathrooms (40% vs. 50%), indoor smoking (24% vs. 31%), and pets (19% vs. 25%). There were major concerns about the risk of getting infected with Covid-19 for both staff (42%) and the home care recipients (50%). There were statistically significant differences between regions, e.g. many problems were more common in the Västerbotten region than in the other two regions during the pandemic, while challenges with protective equipment was most common in the Västernorrland region. Conclusions In-home work environment problems are common for home care workers and worsen in a more strained situation. Efforts are needed to strengthen the work environment for home care workers.